Implementation of an Independent Curriculum in Supporting Students' Freedom to Create and Learn - Quratul Aini; Adiyono (Kirana Publisher (KNPub), 2023)
As one of the efforts to improve the quality of teaching in education, the government is trying to produce various necessary policies. This will be important because until now there is still a gap between reality and expectations of learning quality. Currently, the quality of our learning is not in line with what is expected as the presence of an independent curriculum is expected to strengthen learning transformation efforts. The implementation of the curriculum has been repeatedly carried out improvements and changes as an effort to improve the previous curriculum. This research explains and provides an overview of the implementation of the independent curriculum in supporting creative freedom and learning. The results of this study indicate that the implementation of the curriculum in schools in supporting creative freedom and learning has been implemented optimally and is ongoing, although in its implementation there are still many shortcomings and obstacles. To succeed in implementing an independent curriculum, joint efforts and synergy are needed. The Ministry of Religious Affairs is expected to contribute positively to the implementation of the independent curriculum starting in 2023.